Synthesis and Investigation of the Properties of a Branched Phthalonitrile Containing Cyclotriphosphazene - Dengxun Ren; Zexu Fan; Jiaqu Zhang; Yi Xu; Xianzhong Tang; Mingzhen Xu (Molecules)
To study the properties of cyclotriphosphazene (CTP)-containing phthalonitriles, a branched phthalonitrile containing CTP (CTP–PN) with self-catalytic behavior was designed and synthesized. The structure of CTP–PN was characterized by FT–IR (Fourier transform infrared spectroscopy), MS (mass spectroscopy), 1H–NMR (proton nuclear magnetic resonance spectroscopy), and 13C–NMR (carbon nuclear magnetic resonance spectroscopy). Then, the curing reaction of CTP–PN was studied using DSC (differential scanning calorimetry) and DRA (dynamic rheological analysis). The results show that the curing reaction of CTP–PN is initiated at 200 °C. Additionally, the change in the viscosity of CTP–PN as a function of the temperature was investigated. After curing at different temperatures, the generated structures were characterized by FT–IR. The fracture morphology and thermomechanical properties of cured CTP–PN were scanned and studied using SEM (scanning electron microscopy) and TMA (thermomechanical analysis), respectively. The results demonstrate that CTP–PN exhibits a smooth fracture surface and possesses a relatively low CTE (coefficient of linear thermal expansion) of approximately 25 ppm/°C at 285 °C. A Td5% (temperature at which 5% weight loss occurs) of as high as 405 °C can be obtained for cured CTP–PN, and its char yield at 800 °C exceeds 70% in N2. FT–IR and XPS (X-ray photoelectron spectroscopy) were used to study the thermal decomposition of cured CTP–PN, indicating that it remains stable below 350 °C. With an increasing temperature, there is decomposition first of CTP and P–NH–Ph and C–O–C bonds (>350 °C) and then nitrogen-containing aromatic heterocycles (>500 °C), ultimately resulting in the formation of P-containing residual char.